Acute Myocardial Infarction of the Left Main Coronary Artery Presenting with Cardiogenic Shock and Pulmonary Edema during Noncardiac Surgery. (14th August 2021) - Takenaka, Sakae; Konishi, Takao; Sato, Tomoya; Tada, Atsushi; Koizumi, Takuya; Mizuguchi, Yoshifumi; Kadosaka, Takahide; Motoi, Ko; Kobayashi, Yuta; Komoriyama, Hirokazu; Kato, Yoshiya; Sarashina, Miwa; et al.
Abstract : Acute myocardial infarction (AMI) caused by severe stenosis of left main coronary artery (LMCA) presenting with cardiogenic shock and pulmonary edema during noncardiac surgery is uncommon, but a catastrophic event. A 77-year-old male with cholangiocarcinoma underwent hepatectomy. During the surgery, he presented with cardiogenic shock, which did not respond to infusion administration or vasopressor. A transesophageal echocardiogram revealed anterior, septal, and lateral severe hypokinesia and impaired left ventricular function. Emergent coronary angiogram showed severe stenosis of LMCA. The patient underwent primary percutaneous coronary intervention (PCI) under the support of intra-aortic balloon pump, followed by extracorporeal membrane oxygenation. The chest roentgenogram showed pulmonary edema. Two days after PCI, he successfully underwent hepatectomy and bile duct resection. Early identification of the cause of hemodynamic instability during noncardiac surgery and invasive strategy are important for minimizing the myocardial injury and improving clinical outcomes in AMI of LMCA.